Conceptualizing credibility, relevance and legitimacy for evaluating the effectiveness of science–policy interfaces: Challenges and opportunities. (5th February 2015) - Heink, Ulrich; Marquard, Elisabeth; Heubach, Katja; Jax, Kurt; Kugel, Carolin; Neßhöver, Carsten; Neumann, Rosmarie K.; Paulsch, Axel; Tilch, Sebastian; Timaeus, Johannes; Vandewalle, Marie
Abstract : Credibility, relevance and legitimacy are often cited as determinants of the effectiveness of interfaces between science and environmental policy and serve as criteria for their evaluation. However, these concepts are hazy and have a variety of meanings. In practice, the systematic evaluation of science–policy interfaces according to credibility, relevance and legitimacy is subject to a number of difficulties and is rarely done. In this paper we offer some clarification of these concepts and show how they influence the perception and evaluation of science–policy interfaces. Our findings reveal that, while the attributes of credibility, relevance and legitimacy are helpful when reflecting on the effectiveness of science–policy interfaces, they are difficult to apply as criteria when evaluating these interfaces. To apply these concepts in a meaningful way to the task of evaluation they need to be defined specifically for the particular context of the science–policy interface concerned.